2003
DOI: 10.1074/jbc.m307186200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of an Intermediate in the Alkali Degradation of (6-4) Photoproduct-containing DNA

Abstract: The (6-4) photoproduct formed by ultraviolet light is known as an alkali-labile DNA lesion. Strand breaks occur at (6-4) photoproducts when UV-irradiated DNA is treated with hot alkali. We have analyzed the degradation reaction of this photoproduct under alkaline conditions using synthetic oligonucleotides. A tetramer, d(GT(6-4)TC), was prepared, and its degradation in 50 mM KOH at 60°C was monitored by high performance liquid chromatography. A single peak with a UV absorption spectrum similar to that of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 34 publications
3
28
0
Order By: Relevance
“…Moreover, formation of 1 is consistent with findings reported upon the hydrolysis of 6-4PP, where the N3–C4 bond of the 5′-thymine ruptures. 12 We thus conclude that the new product observed in the chromatogram shown in Figure 2 A is most likely a water adduct possessing the structure shown for 1 (Scheme 1 ).…”
Section: Resultsmentioning
confidence: 70%
“…Moreover, formation of 1 is consistent with findings reported upon the hydrolysis of 6-4PP, where the N3–C4 bond of the 5′-thymine ruptures. 12 We thus conclude that the new product observed in the chromatogram shown in Figure 2 A is most likely a water adduct possessing the structure shown for 1 (Scheme 1 ).…”
Section: Resultsmentioning
confidence: 70%
“…To make abasic (AP) sites, oligonucleotides containing a single uracil residue were treated with uracil DNA glycosylase and substrates prepared as above. AP sites were confirmed by conversion to breaks (Higurashi et al 2003) (Fig. S1).…”
Section: Methodsmentioning
confidence: 75%
“…We recently revealed that the first reaction in the alkali degradation of the photoproduct is hydrolysis of the N3-C4 covalent bond of the 5 0 base moiety [50]. Although the (6-4) photoproduct can be formed at all four of the dipyrimidine sites [49], its frequency is higher at the TC and CC sites [48,51,52], and 5-methylcytosine inhibits the formation of this type of lesion [52].…”
Section: The (6-4) Photoproducts and Their Dewar Valence Isomersmentioning
confidence: 99%